Experiences and Perpetration of Recent Intimate Partner Violence Among Women and Men Living in an Informal Settlement in Nairobi, Kenya: A Secondary Data Analysis. Issue 1 (January 2022) - Ringwald, Beate; Kababu, Margaret; Ochieng, Christian B.; Taegtmeyer, Miriam; Zulaika, Garazi; Phillips-Howard, Penelope A.; Digolo, Lina
Evidence suggests an overlap between intimate partner violence (IPV) experience and perpetration. However, few studies in sub-Saharan Africa have investigated experience and perpetration of IPV among women and men within the same community. This study reports prevalence of past-year IPV experience and perpetration among women and men living in an informal settlement in Nairobi, Kenya, and factors associated with IPV. Data analyzed for this study involved a geographically distributed random sample of 273 women and 429 men who participated in a community survey. We approximated prevalence of IPV experience and perpetration and used logistic regression for estimating associations between individual-level factors and IPV. Women and men experienced similar levels of IPV, but a significantly higher proportion of men reported physical and sexual IPV perpetration. Witnessing violence between parents in childhood was associated with women's physical and sexual, and men's sexual IPV experience; and with women perpetrating emotional, and men perpetrating sexual IPV. Less equitable gender attitudes were associated with men's perpetration of physical IPV. More equitable gender knowledge was associated with women's experience of sexual IPV, and with men perpetrating IPV. Perceived skills to challenge gender inequitable practices were negatively associated with men perpetrating sexual IPV. In conclusion, we found IPV experience and perpetration were highly correlated, and that, contrary to commonly reported gender gaps, men and women experienced similar rates of IPV. We make suggestions for future research, including on IPV prevention interventions in areas with such IPV prevalence that would be beneficial for women and men and future generations.